Parametric management of economic actor behaviour under bounded rationality - A. YU. Obydenov (Стратегические решения и риск-менеджмент)
The article explores parametric management of economic entity production volume within framework of weak and strong hypothesis of bounded rationality. The concept of parametric management with the example of economic entity behavior modeling under the conditions of bounded rationality is considered. The qualitative analysis of nonlinear kinetics differential equations is applied as the basic method of the investigation suggested. The investigation proves the possibility of parametric stimulation of economic entity production volume increasing by the means of: transfers, taxes, fixed prices depending on different conditions, such as the model of economic entity rationality, demand function, borrowing financial assets accessibility. The invariant instruments of parametric management for different models of economic actors strategic behavior are proposed. The managerial problems explored may be generalized for solving the coordination problem as a hole.